2005
DOI: 10.2174/138955705774575264
|View full text |Cite
|
Sign up to set email alerts
|

Are Vanadium Compounds Drugable? Structures and Effects of Antidiabetic Vanadium Compounds: A Critical Review

Abstract: Vanadate can be bioequivalent to phosphate and replace it in cellular metabolism. The detection of insulin-like activity has spurred interest in the development of oral anti-diabetic drugs containing vanadium. We collected and evaluated a vast toxicity data set and discussed molecular aspects related to insulin-mimetic effects of vanadium complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 98 publications
0
38
0
2
Order By: Relevance
“…Recently, Scior et al critically reviewed the question of the drugability of vanadium compounds and concluded that vanadium is a drugable agent. It is, however, essential to develop more potent vanadium compounds with higher efficacy and reduced side effects [8]. Vanadium efficacy can be increased by synthesis of organic vanadium chelates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Scior et al critically reviewed the question of the drugability of vanadium compounds and concluded that vanadium is a drugable agent. It is, however, essential to develop more potent vanadium compounds with higher efficacy and reduced side effects [8]. Vanadium efficacy can be increased by synthesis of organic vanadium chelates.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be interpreted against the hypothesis of prodrug function which cannot be ruled out for the more unstable organic vanadium compounds. 46 With regard to the patented compounds, [77][78][79][80][81] an enhanced pharmacokinetic and dynamic drug profile of TSAG0101 can be expected; due to its experimental complex stability and theoretical binding specificity. In biological assays in rats, TSAG0101 showed insulin-like activity (insulin mimesis), also no pancreatic component could be observed, ie, its blood glucose lowering effect is of extrapancreatic nature.…”
Section: Discussionmentioning
confidence: 99%
“…The former imitates the geometry of a phosphate anion, phosphatomimetic group, 46 whereas the latter is composed of unrelated organic rests (strong chelating groups). To this end, pharmacologically and chemically known molecular fragments (A, B, and Q in Figure 2) were combined to build an imaginary compound using Chem3D of the ChemOffice 5.0 tool box.…”
Section: De Novo Designmentioning
confidence: 99%
See 2 more Smart Citations